Studi Korelasi: Perilaku Penyimpanan dan Penyajian Makanan dengan Kejadian Diare pada Balita - Puji Lestari; Liyanovitasari; Mona saparwati (Pro Health Jurnal Ilmiah Kesehatan, 2023)
According to the World Health Organization (WHO) diarrheal disease is the second cause of death in children under five years old and is a potential endemic disease of Extraordinary Events (KLB) which is often accompanied by death in Indonesia. Food can be one of the causes of food poisoning and can be an intermediary in the transmission of diseases including diarrheal diseases. The purpose of this study was to determine the relationship between food storage and presentation behavior with the incidence of diarrhea in toddlers. This study is a correlation study with a cross sectional approach. The variables i.e. storage and presentation of food and incidence of diarrhea were measured using questionnaires. Food storage and presentation includes washing cutlery, selecting foodstuffs, how to cook food and drinking water and how to store food. The population in this study was mothers of toddlers. The respondents of the study as many as 156 toddlers were taken by purposive sampling technique. Data analysis was carried out with chi square test. Research Results: Based on the results of the study, the characteristics of respondents were 77 respondents (49.4%) male and 79 respondents (50.6%) female, 56 (38.9%) aged 12-23 months, 52 (33.3%) aged 24-35 months, 48 (30.8) aged 36-53 months. There is a significant relationship between food storage and serving with the incidence of diarrhea with a meaning value of p = 0.005. It is expected that mothers can pay attention to the storage and presentation of food to prevent an increase in the incidence of diarrhea.   ABSTRAK                 Menurut World Health Organization (WHO) penyakit diare merupakan penyebab kematian kedua pada anak di bawah lima tahun dan merupakan penyakit endemis potensial Kejadian Luar Biasa (KLB) yang sering disertai dengan kematian di Indonesia. Makanan bisa menjadi salah satu penyebab terjadinya keracunan makanan dan dapat menjadi perantara dalam penularan penyakit termasuk penyakit diare. Tujuan penelitian ini adalah untuk mengetahui hubungan perilaku penyimpanan dan penyajian makanan dengan kejadian diare pada balita. Penelitian ini adalah penelitian korelasi dengan pendekatan cross sectional. Variabel yaitu penyimpanan dan penyajian makanan dan kejadian diare diukur dengan menggunakan kuesioner. Penyimpanan dan penyajian makanan meliputi pencucian alat makan, pemilihan bahan makanan, cara memasak makanan dan air minum serta cara penyimpanan makanan. Populasi dalam penelitian ini adalah ibu balita. Responden penelitian sebanyak 156 balita diambil dengan teknik sampling purposive sampling. Analisa data dilakukan dengan uji chi square. Berdasarkan hasil penelitian didapatkan  karakteristik responden sebanyak 77 responden (49,4 %) berjenis kelamin laki laki dan 79 responden (50,6 %) berjenis kelamin perempuan, usia responden 12-23 bulan sebanyak 56 (38,9%), usia 24-35 bulan sebanyak 52 (33,3%), usia 36-53 bulan sebanyak 48 (30,8). Ada hubungan yang bermakna antara penyimpanan dan penyajian makanan dengan kejadian diare dengan nilai kemaknaan p=0,005. Diharapkan ibu dapat memperhatikan penyimpanan dan penyajian makanan untuk mencegah terjadinya peningkatan kejadian diare.